2016
DOI: 10.4236/aim.2016.611082
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Comparative Cervical Tuberculin Test and Serological Methods with Culturing of Nasal Swab in Diagnosis of Bovine Tuberculosis in Cross Breed Cattle Baghdad Iraq: A Comparative Evaluation

Abstract: This study was designed to assess the diagnostic value of Rapid Antigen bovine TB antibody test kit (RAT) and any association with cervical comparative tuberculin test (CCTT), (iELISA) and nasal swabs culturing, among based detection of M. bovis infection. A herd of 21 animals aged 1-8 years cross bread cattle of college of veterinary medicine. 19 (90.47%) animals had good body condition scores, two bulls included, and 2 (9.52%) cows were fair. Serum samples were collected, analyzed for anti-bovine TB antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In the current study, the overall prevalence was 12.2% (18.9% in cattle). In Baghdad, the prevalence in cattle was 19% [15] , which is close to what is reported here. However, in Was it, the prevalence was reported at 75% [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, the overall prevalence was 12.2% (18.9% in cattle). In Baghdad, the prevalence in cattle was 19% [15] , which is close to what is reported here. However, in Was it, the prevalence was reported at 75% [12].…”
Section: Discussionsupporting
confidence: 88%
“…Those studies indicated an increased trend in the prevalence of the disease in the area. In Baghdad, Mycobacterium bovis was detected in cow's milk [14], and the prevalence of the infection in cattle sera was 19% [15]. In Mosul, however, the epidemiologic situation of the disease is not known in cattle and buffalos.…”
Section: Introductionmentioning
confidence: 99%